(3ebGdI GdYde aj GdLeY Hjf QCjj CadGWhf hCQSWh aj MOhK GdYGdes - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s; (3GdaGQCHj GdeYde GdKGfj , CHh fUQ eMeO Hf WQNGf GdaGQGHj, CHh fUQ GdaGQCHj,J (B339 (3g` s
(3ChdgG (B:s
(3ebGdI CHj fUQ GdaGQGHi ai GdLeY Hjf QCjj CadGWhf hCQSWh s
(3BNQgG (B:s
(3ai GdC hd hdc GSJNQGL HGbi GdCeKdI Edi eG HjffG hdfbJUQ Ydi gPG GdbOQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3LeYs
Keywords: (3GdadSaI hGdefWbs